Protein and lipid oxidation of low‐salt dry‐cured black carp (Mylopharyngodon piceus) during storage: Biochemical changes and shelf life prediction - Jia, Shiliang; Zhu, Yiming; Huang, Aixia; Chu, Yushan; Ding, Yuting; Zhou, Xuxia; Ke, Zhigang (Journal of food processing and preservation, 2022)
With the demand for the reduction in sodium consumption, low‐salt dry‐cured fish as a traditional preserved food has gained growing popularity. However, the salt reduction affects adversely the shelf‐life of dry‐cured fish. This study aimed at evaluating the quality changes of low‐salt dry‐cured black carp packaged under vacuum during storage and constructing a predictive model for the shelf life based on quality indicators. Four‐degree Celcius storage delayed the lipid and protein oxidation in comparison with that of 25°C, and the sensorial shelf life of the dry‐cured black carp stored at 4 and 25°C were 20 and 30 days, respectively. The odor was found to be more sensitive in revealing the quality deterioration among all sensorial indicators. Pearson correlation analysis showed that the TBARS and TVC value had a higher correlation with the sensory score, and the shelf life predictive model based on TBARS and TVC value showed high accuracy, indicating the predictive model constructed is effective for predicting the shelf life of low‐salt dry‐cured black carp. Novelty impact statement Four‐degree celcius (4°C) of storage can delay the process of protein and lipid oxidation, and the odor is sensitive in revealing the quality deterioration of low‐salt dry‐cured black carp. The TBARS and TVC values have a higher correlation with sensory quality, and the predictive models based on TBARS and TVC can be a reliable tool for shelf life prediction.